The effect of innovation and modernization as an approach to strategic change in the efficiency of organizational performance Field research in the Oil Projects Company (SCOP( - Abdullah Al-Hamdani, Yousif Olaiwe; Kadhim, Faik Jawad (Journal of Economics and Administrative Sciences, 2021)
The purpose of this research is to improve the organizational performance of the Oil Projects Company by adopting an approach to strategic change، and finding appropriate solutions to the problems facing the company. The researcher adopted in designing his research by conducting a survey of previous literature that dealt with approaches to strategic change، as the results of the survey showed that most researchers agree on the approach of renewal and modernization، Which formed a starting point for the researcher to identify the extent of the company’s management interest in renewal and modernization to improve its level of performance، and the quality of the procedures followed on the ground that is related to these two variables، With regard to the research methodology، the researcher relied in his current study on the (analytical descriptive approach) in order to achieve the objectives of the research، by based on determining the characteristics of the researched phenomenon، giving it a (numeric) description، and determining the nature of the relationship between the two research variables to reach the field problem and identify on it in the Reality. This approach was based on collecting data from the research sample، classifying it، analyzing it، and interpreting it. In addition to explaining the influence relationship between the two variables of the research to reach the results، as for the most important tools that have been used in this approach، What has been written in the literature on the phenomenon researched، including books، articles، to cover the theoretical side، and on the field level، the researcher used the questionnaire as the main tool in collecting data from the research sample، and at various administrative levels، as the sample members were represented by the leaders working in the company’s centre ، whose number is (85) individuals، and the researcher conducted personal interviews with a number of them، and asked questions and inquiries that are related to the subject of the research، in order to obtain accurate information about the actual reality of the researched company. The researcher used (the arithmetic mean، standard deviation، coefficient of variation and relative importance، and simple linear regression) in the data analysis. The results of the research showed that there is a correlation between the approach of renewal and modernization and organizational performance، and as for the relationship of influence، despite the influence of the approach of renewal and modernization on organizational performance، but at the same time it requires a greater level of attention، and the researcher recommended that the company’s management focus their interest in renewal and modernization، in addition to drawing procedures that have a positive impact in enhancing the company’s ability to advance its reality and improve its level of performance in practice and achieve efficiency and effectiveness. The originality of this research lies in the fact that it is based on modern sources and scientific sober، which formed a reference for the researcher، in addition to linking innovation and modernization، as an approach to strategic change to organizational performance in its two dimensions (efficiency and effectiveness)، since no such research has been carried out before and applied it to solve the dilemma of a governmental organization working in the field of the oil industry، in practical terms، this research contributed to the creation of new methods of work that greatly contribute to solving the problems that most public sector organizations face in the Iraqi environment